Phosphoric Acid and Steam as Activation Agents for Carbonized Porous Polymer Surfaces - M. Sobiesiak; B. Gawdzik; A.M. Puziy; O.I. Poddubnaya (Adsorption Science & Technology)
Carbon sorbents derived from the copolymer of 4,4′-bis(maleimidodiphenyl)methane and divinylbenzene are described. The influence of phosphoric acid treatment and the type of carrier gas used in the carbonization process were studied. Solid-phase extraction experiments were conducted to determine their impact on the sorption properties of these new sorbents. The recoveries and breakthrough volumes for phenolic compounds preconcentrated from water were studied.